İlköğretim 6. sınıf resim derslerinde üç boyut kavramı - Karatop Funda (My University, 2005)
Hazırlanan bu tez çalışmasında 6. sınıf olan 12 yaş grubu öğrencilerinin resim çalışmalarında üç boyut etkisini verebilmelerine yardımcı olacak yöntemler üzerinde araştırma yapılmıştır. Hacmin sanat eğitimi programında ve öğretimde değerlendirilmesi gereken yönleri açıklanmaya çalışılmıştır. Yapılan etkinliklerde üç boyutlu malzemelerden ve üç boyut etkisi olan çalışmalardan faydalanıldığı gibi gözleme dayalı çalışmalar da yaptırılmıştır. Resim sanatı tarihinden üç boyutun gelişimi ile ilgili bilgi verilmesiyle başlanan araştırmada, sanat tarihinde üç boyut etkisini veren ressamlardan örnekler gösterilerek farklı yöntemlerin kullanılabileceği ortaya konmuştur. Öğrencilerin üç boyutu algılayış biçimleri ve gelişim evreleri incelenerek ilköğretim ikinci kademe öğrencilerinin yaş dönemleri ve psikolojik yapıları dikkate alınmıştır. İlköğretim 12 yaş grubu olan öğrencilerin çalışmalarına yer verilerek ilköğretim 6.sınıf resim iş ve iş eğitimi dersleri müfredat lantı kurulmuştur. Bunun yanında, farklı çevrelerde yer alan iki ayrı okulun 6. sınıf öğrencilerinin aynı yaş grubu olmalarına rağmen farklılıklar gösterdiği gözlenmiş, bu farklılıklar dikkate alınarak çevre koşullarına uygun öğretme teknikleri geliştirilmiştir. Yaş dönemleri itibarı ile duyguların yoğun ve karmaşık yaşandığı erinlik döneminin başlangıcı olan 6.sınıf öğrencilerine uygulatılacak plastik sanat eğitimi programının, onları kısıtlamadan, yaratıcılıklarını arttırıcı nitelikte olması gerekmektedir. Her öğrencinin yaratıcı gücünü geliştirmeyi hedef alan sanat eğitimi programında üç boyutlu çalışmalara yer verilmesi, öğrencilerin sanatsal ve yaratıcı düşüncelerinin gelişimine de katkıda bulunacaktır. Üç boyut etkisini vermeye çalışırken çocuk, resimde renk, espas, perspektif, ışık- gölge gibi kavramların farkına varacaktır. Bu kavramlar ve uygulamalar da çocuğun resmini zenginleştirecek ve resim zenginleştikçe kullandığı teknik ve hayal gücü de aynı oranda artacaktır. Yani öğrencinin becerilerini sunma konusundaki başarısı onu güçlendirecektir. Kendine güvenen bir öğrenci daha çok üretmek isteyecek ve yaratıcılığını arttıracaktır. Bu noktada sanat eğitimcisinin öğrencilere olan tutumu ve resim çalışmalarını değerlendirme biçimi büyük önem taşımaktadır. Bu tez çalışması ilköğretim 6. sınıf öğrencilerinin üç boyutu algılayış ve uygulayış biçimleri ve hacim kavramının geliştirilmesi için bir rehber olabilmek çabası ile hazırlanmıştır.

The aim of the thesis that is prepared is to teach volume to twelve-age group students that study sixth class and to make them give the effect of three dimension in their art works. It has been tried to explain the required aspects of the volume in arts education programme. In the activities, besides having benefited from the three dimensional materials and the works which have three dimesnional effects, works that are based on observation had been held as well. At first, information had been given about the improvement of three dimension in painting arts history, by giving examples of painters it had been displayed that different methods can be used. The ways that the students perceive three dimension had been analyzed, the age and psychological situation of secondary class students of primary school had been taken into consideration. There had been correlation between the curriculum and the art works of sixth classes by giving place to the art works of the twelve-age group students. Besides, it had been observed that sixth class students from different school neighbourhood show difference although they from are the same age group, taking these differences into consideration teaching technics had been developed according to the conditions of the environment. In sixth classes, because of their age periods , the beginning of adolescence when the emotions are intense and complicated the visual arts education should be in a way which will not restrict them and increase their creativity. Giving place to three dimensional works in arts studies which aim to improve each students’ creativity will contribute to their artistic and creative ideas. While trying to give the effect of three dimension to their work, children will learn the concepts such as colour, espace, perspective, light and shadow. These concepts and applications will enrich the children’s paintings, proportionally the techincs they use and their creativity will increase. It means that the students’ success while presenting their talents will make them strong. As self-confident students they will want to produce more and increase their creativity. At this point the arts teacher’s behaviours and the way s/ he evaluate the arts work has big importance. This thesis is prepared in diligence of being a guide to improve the sixth class students' perceivement of three dimension and the ways that it is applied. SUMMARY The aim of the thesis that is prepared is to teach volume to twelve-age group students that study sixth class and to make them give the effect of three dimension in their art works. It has been tried to explain the required aspects of the volume in arts education programme. In the activities, besides having benefited from the three dimensional materials and the works which have three dimesnional effects, works that are based on observation had been held as well. At first, information had been given about the improvement of three dimension in painting arts history, by giving examples of painters it had been displayed that different methods can be used. The ways that the students perceive three dimension had been analyzed, the age and psychological situation of secondary class students of primary school had been taken into consideration. There had been correlation between the curriculum and the art works of sixth classes by giving place to the art works of the twelve-age group students. Besides, it had been observed that sixth class students from different school neighbourhood show difference although they from are the same age group, taking these differences into consideration teaching technics had been developed according to the conditions of the environment. In sixth classes, because of their age periods , the beginning of adolescence when the emotions are intense and complicated the visual arts education should be in a way which will not restrict them and increase their creativity. Giving place to three dimensional works in arts studies which aim to improve each students’ creativity will contribute to their artistic and creative ideas. While trying to give the effect of three dimension to their work, children will learn the concepts such as colour, espace, perspective, light and shadow. These concepts and applications will enrich the children’s paintings, proportionally the techincs they use and their creativity will increase. It means that the students’ success while presenting their talents will make them strong. As self-confident students they will want to produce more and increase their creativity. At this point the arts teacher’s behaviours and the way s/ he evaluate the arts work has big importance. This thesis is prepared in diligence of being a guide to improve the sixth class students' perceivement of three dimension and the ways that it is applied.
Keywords: Eğitim, Resim; Resim Becerileri, İlköğretimde